Pendampingan Pengembangan Program Pojok Baca Kelas Di Madrasah Ibtidaiyah Muhammadiyah 01 Pekanbaru - Ramanda Rizky; Syahdan Syahdan; Suharni Suharni (Unika Santu Paulus Ruteng, 2024)
The habit of reading should be introduced to children at an early age for them to continue reading throughout their lives. A well-planned and facilitated program for habituating readers is therefore necessary. This Community Service activities aim to provide assistance for the development of the Class Reading Corner Program at Madrasah Ibtidaiyah Muhammadiyah 01 Pekanbaru. Following a review of the school's problems regarding the lack of reading corners, a limited number of children's reading books, and the lack of governance of class reading corners, these activities were carried out based on the results of an analysis of these problems. As part of this program, 48 sets of children's picture books were handed over, including mini bookshelves. The program also socialized development of reading corner program and made a simulation of making picture books involving 14 teachers, 1 administrative staff, and 1 headmaster. This program employed a direct observation and questionnaire for the evaluation. The observation showed that three classroom reading corners are present and in use at the school. A satisfaction level of 89.6% was obtained from activity participants after analyzing the questionnaire, an increase of 29.20% over that obtained prior to socialization and simulation. Furthermore, 93.75 % of the participants wanted a reading corner and 100% indicated that there was a need to enhance or improve its quality. The results from these studies suggest that this mentoring program has achieved a positive effect by raising awareness of the importance of increased reading proficiency in schools.